Characteristics of patients with autonomic dysfunction in the Transthyretin Amyloidosis Outcomes Survey (THAOS). (3rd July 2022) - Barroso, Fabio A.; Coelho, Teresa; Dispenzieri, Angela; Conceição, Isabel; Waddington-Cruz, Marcia; Wixner, Jonas; Maurer, Mathew S.; Rapezzi, Claudio; Planté-Bordeneuve, Violaine; Kristen, Arnt V.; González-Duarte, Alejandra; Chapman, Doug; et al.
Abstract: Background: Autonomic dysfunction is common in transthyretin amyloidosis (ATTR amyloidosis), but its frequency, characteristics, and quality-of-life (QoL) impact are not well understood. Methods: The Transthyretin Amyloidosis Outcomes Survey (THAOS) is an ongoing, global, longitudinal survey of patients with ATTR amyloidosis, including patients with inherited (ATTRv) and wild-type (ATTRwt) disease and asymptomatic patients with TTR mutations (ClinicalTrials.gov: NCT00628745). In a descriptive analysis, characteristics and Norfolk QoL-DN total (TQoL) scores at enrolment were compared in patients with vs without autonomic dysfunction (analysis cut-off: 1 August 2020). Results: Autonomic dysfunction occurred in 1181/2922 (40.4%) symptomatic patients, and more commonly in ATTRv (1107/1181 [93.7%]) than ATTRwt (74/1181 [6.3%]) amyloidosis. Time (mean [SD]) from ATTR amyloidosis symptom onset to first autonomic dysfunction symptom was shorter in ATTRv (3.4 [5.7] years) than ATTRwt disease (9.7 [10.4]). In ATTRv disease, patients with vs without autonomic dysfunction had worse QoL (TQoL, 47.3 [33.2] vs 16.1 [18.1]); in ATTRwt disease, those with vs without autonomic dysfunction had similar QoL (23.0 [18.2] vs 19.9 [20.5]). Conclusions: Autonomic dysfunction was more common and presented earlier in symptomatic ATTRv than ATTRwt amyloidosis and adversely affected QoL in ATTRv disease. These THAOS findings may aid clinicians in diagnosing and treating patients with ATTR amyloidosis. Trial registration: ClinicalTrials.gov: NCT00628745